Aquisição de sujeitos e objetos pronominais no português brasileiro : um estudo longitudinal dos nulos, pessoais e seus casos na perspectiva da morfologia distribuída - Bulla, Julieane Pohlmann (2014)
This thesis investigates the acquisition of personal pronouns in Brazilian Portuguese (BP) from the perspective of Distributed Morphology. Based on a corpus composed by interactions of 3 toddlers recorded naturalistic and periodically from 1 year and 7 months to the age of 3, the study presents quantitative and qualitative data of the production of personal pronouns in subject and object positions, as well as null and overt subject and object production. From morphosyntactic analyses of 1st person contexts, it was found that the children in this corpus do pass through an Optional Person Stage, during which they alternate between agreeing inflected verbs and default inflected ones, being the last identical to 3rd person inflected forms. Exploring the morphological case issue, only two cases came out in the acquisition of BP: the accusative, responsible by the insertion of the clitics me and te; and the oblique, causing the insertion of the stressed pronouns mim and ti. It is proposed that case attribution may take place via Lowering Morphological Merger: accusative case is given to 1st and 2nd person pronouns which are VP-internal and oblique case to 1st and 2nd person pronouns that are PP-internal. After the accusative item insertion, there may still be the action of Local Dislocation Morphological Merger to rearrange the pronoun to a proclitic position, typical of BP. Thus, this research has contributed with longitudinal data of pronoun and verbal inflection acquisition by Brazilian children, what may engage future investigations, including those which compare the acquisition of these aspects by other languages speaking children